(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Planktonic foraminifera were studied in the upper Albian to Cenomanian sedimentary sequence of the Monte Petrano and Le Brecce stratigraphic sections located in the Umbria-Marche Basin (central Italy), and of Hole 547A and Site 545 drilled by the Deep Sea Drilling Project (DSDP) on the Mazagan Plateau (offshore Morocco, northeast Atlantic Ocean). Biostratigraphic results allow the identification of a stratigraphically ordered sequence of bioevents that have proved to be reliable for regional and interregional correlations, from older to younger: the lowest occurrences (LOs) of Th. appenninica, Pl. buxtorfi, Pa. libyca, Th. brotzeni in the Albian, and the LOs of Th. globotruncanoides, Th. greenhornensis and Rt. cushmani in the Cenomanian sediments. We remark the difficulty in the identification of the Th. reicheli Zone used in the Tethyan biozonation because of the rarity and absence of the species in many low to mid- latitude pelagic sequences. To overcome the problem, we use the Th. greenhornensis Zone defined as the stratigraphic interval between the lowest occurrence (LO) of Th. greenhornensis and the LO of Rt. cushmani. The LO of Th. greenhornensis is a solid bioevent with the nominal species characterized by a wide geographic distribution and occurring close to the LO of Th. reicheli where the latter species is present. The studied stratigraphic sections are compared with the coeval Mont Risou section in the Vocontian Basin and the record from Blake Nose in the western North Atlantic to verify the correlation and synchronicity of biostratigraphic and chemostratigraphic events including the Oceanic Anoxic Events 1d (OAE1d) and the Mid Cenomanian Event (MCE).